Reconsidering the relationship between foreign direct investment and growth. (18th May 2019) - Encinas-Ferrer, Carlos; Villegas-Zermeño, Eddie
It has been assumed that foreign direct investment (FDI) is a variable that explains economic growth (EG). As investment (I) is the dynamic element of gross domestic product (GDP), therefore, FDI, as part of total investment, should be also the independent variable and GDP growth the dependent one. However, many studies in many countries have shown the contrary, there is not such a causal relationship between FDI and GDP. In our investigation, we include the study of the cases of Mexico, China, Brazil and the Republic of Korea. It is our hypothesis that there is not a causal relationship between FDI, as the independent variable, and GDP growth as the dependent one in the selected countries and that this is in part because FDI is a small proportion of total (national and foreign) direct investment and so its impact is reduced.